Dosimetric characteristics of electron beams produced by two mobile accelerators, Novac7 and Liac, for intraoperative radiation therapy through Monte Carlo simulation. (7th January 2013) - Righi, Sergio; Karaj, Evis; Felici, Giuseppe; Di Martino, Fabio
Abstract : The Novac7 and Liac are linear accelerators (linacs) dedicated to intraoperative radiation therapy (IORT), which produce high energy, very high dose‐per‐pulse electron beams. The characteristics of the accelerators heads of the Novac7 and Liac are different compared to conventional electron accelerators. The aim of this work was to investigate the specific characteristics of the Novac7 and Liac electron beams using the Monte Carlo method. The Monte Carlo code BEAMnrc has been employed to model the head and simulate the electron beams. The Monte Carlo simulation was preliminarily validated by comparing the simulated dose distributions with those measured by means of EBT radiochromic film. Then, the energy spectra, mean energy profiles, fluence profiles, photon contamination, and angular distributions were obtained from the Monte Carlo simulation. The Spencer‐Attix water‐to‐air mass restricted collision stopping power ratios ( s W, air ) were also calculated. Moreover, the modifications of the percentage depth dose in water (backscatter effect) due to the presence of an attenuator plate composed of a sandwich of a 2 mm aluminum foil and a 4 mm lead foil, commonly used for breast treatments, were evaluated. The calculated s W, air values are in agreement with those tabulated in the IAEA TRS‐398 dosimetric code of practice within 0.2% and 0.4% at z ref (reference depth in water) for the Novac7 and Liac, respectively. These differences are negligible for practical dosimetry. The attenuator plate is sufficient to completely absorb the electron beam for each energy of the Novac7 and Liac; moreover, the shape of the dose distribution in water strongly changes with the introduction of the attenuator plate. This variation depends on the energy of the beam, and it can give rise to an increase in the maximum dose in the range of 3%–9%. PACS number: 87.56.‐v